Aptamers: A Feasible Technology in Cancer Immunotherapy - M. M. Soldevilla; H. Villanueva; F. Pastor (Journal of Immunology Research)
Aptamers are single-chained RNA or DNA oligonucleotides (ODNs) with three-dimensional folding structures which allow them to bind to their targets with high specificity. Aptamers normally show affinities comparable to or higher than that of antibodies. They are chemically synthesized and therefore less expensive to manufacture and produce. A variety of aptamers described to date have been shown to be reliable in modulating immune responses against cancer by either blocking or activating immune receptors. Some of them have been conjugated to other molecules to target the immune system and reduce off-target side effects. Despite the success of first-line treatments against cancer, the elevated number of relapsing cases and the tremendous side effects shown by the commonly used agents hinder conventional treatments against cancer. The advantages provided by aptamers could enhance the therapeutic index of a given strategy and therefore enhance the antitumor effect. Here we recapitulate the provided benefits of aptamers with immunomodulatory activity described to date in cancer therapy and the benefits that aptamer-based immunotherapy could provide either alone or combined with first-line treatments in cancer therapy.